Childhood Physical and Sexual Abuse as a Predictor of Reoffending: A Systematic Review. (July 2021) - Dalsklev, Madeleine; Cunningham, Twylla; Dempster, Martin; Hanna, Donncha
Experiences of childhood trauma such as physical and sexual abuse are common among offender populations, and a trauma history is related to increases in the risk of criminal conduct. Previous reviews on the link between childhood trauma and reoffending are limited in scope as they only investigate adolescent populations. The aim of the current systematic review was to explore the association between childhood physical and sexual abuse and its prediction on actual reoffending rates in adult population(s). Four databases (PsycINFO, Web of Science, PubMed, and PILOTS) were searched, and the final included articles were quality assessed by two reviewers. A total of 3, 151 studies were identified, and 13 met the a priori eligibility criteria. Most of the studies obtained high quality ratings. A narrative synthesis of the results suggests that childhood physical and sexual abuse are generally high among the prison population and tend to be even higher among those who reoffend. A substantial number of studies found that childhood physical and sexual abuse predict reoffending, and the majority of the studies found a positive direction for this association, albeit of a small magnitude. These findings suggest that prisons should consider trauma-informed assessment and rehabilitation of offenders.